"To Work out their own Salvation": Māori Constitutionalism and the Quest for Welfare - Stephens, Māmari (Victoria University of Wellington Law Review, 2015)
New Zealand recently celebrated 75 years of the implementation of the welfare state in 1938. While debate continues about the nature and effectiveness of state welfare provision, welfare is arguably a matter of constitutional concern in New Zealand. Further examination of New Zealand legal history also shows that the welfare of Māori is indeed a matter of deep constitutional concern to Māori, who have consistently sought legislative and extra-legislative ways to have public power used for broad Māori welfare concerns. It is possible to identify a kind of Māori welfare constitutionalism at work, that is arguably in tension with the thinking and practice that produced the welfare state.